Historical, linguistic and religious considerations about the names of the Evangelic Magi: Prolegomena to the redaction of a Namenbuch (Atti del Sodalizio Glottologico Milanese, 2017)
In his still superb article dedicated to the Magi (Mages), published in the 10th volume of the Dictionnaire d’archéologie chrétienne et de liturgie (Paris 1931), Henri Leclerq sharply wrote: “La liste des noms des mages dans les diverses langues et dans les diverses littératures serait assez longue et, jus qu’à présent, ces noms n’ont pas été suffisamment établis et discutés”. Exactly after eightyfive years from that crude statement we can affirm that, notwithstanding the publication of many ad di tional sources, the situation is still the same. The present articles offers a wide-ranging conspectus of the traditions concerning their names in the framework of the different Christian traditions. KEYWORDS: Magi, Zoroastrianism, Christian propaganda, Early Christianity, Gospels